2018
DOI: 10.1016/j.euroecorev.2018.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation in public good games. Calculated or confused?

Abstract: Recent experiments suggest that contribution decisions in a public goods game (PGG) are more likely to be cooperative if based on intuition rather than reflection. This paper (i) reinvestigates the behavioral impact of so-called cognitive style in the PGG; and (ii) connects it with an earlier literature on the role of cognitive failure (confusion). This is motivated by the possibility that the method of time pressure, commonly used to identify cognitive style, invites confusion as a confounding factor. Two cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 81 publications
(97 reference statements)
0
18
1
Order By: Relevance
“…A similar warm-up procedure was followed by Isler, Maule and Starmer (2018), who also found that time pressure increases cooperation. In contrast to this line of research, however, there have also been two studies finding a negative effect of time pressure on cooperation: Capraro & Cococcioni (2016) found that extreme time pressure leads to less cooperation; Goeschl and Lohse (2018) found that time pressure leads to more free-riding in the one-shot public goods game. However, the former work had the limitation that time constraints were added in the instruction screen, and this might have interacted with participants' level of comprehension; whereas the latter work had very high non-compliance rate (43%).…”
Section: Review Of the Empirical Evidencementioning
confidence: 90%
See 1 more Smart Citation
“…A similar warm-up procedure was followed by Isler, Maule and Starmer (2018), who also found that time pressure increases cooperation. In contrast to this line of research, however, there have also been two studies finding a negative effect of time pressure on cooperation: Capraro & Cococcioni (2016) found that extreme time pressure leads to less cooperation; Goeschl and Lohse (2018) found that time pressure leads to more free-riding in the one-shot public goods game. However, the former work had the limitation that time constraints were added in the instruction screen, and this might have interacted with participants' level of comprehension; whereas the latter work had very high non-compliance rate (43%).…”
Section: Review Of the Empirical Evidencementioning
confidence: 90%
“…No effect of Pressure vs Delay on the whole sample. Pressure increases cooperation, among participants who respect the time constraint Everett et al (2017) Prisoner's dilemma Pressure increases cooperation, compared to delay, also towards competitive out-groups Goeschl & Lohse (2018) Public goods game Pressure decreases cooperation Alós-Ferrer & Garagnani (2018) Public goods game Pressure increases cooperation among prosocial participants; Pressure has no effect on individualist participants; Pressure decreases cooperation among competitive participants Bird et al (2019) Public Goods Game among males…”
Section: Dependent Variablementioning
confidence: 99%
“…They replicated the effect that time pressure increases cooperation, but only when participants who fail to comply with the time constraint are excluded from the analysis; they concluded that the positive effect of time pressure on cooperation is best explained in terms of selection bias. Two works even found the opposite effect: Capraro & Cococcioni (2016) found that extreme time pressure leads to less cooperation in the one-shot prisoner's dilemma, Goeschl and Lohse (2018) found that time pressure causes more free-riding in the one-shot public goods game. However, the former work had the limitation that time constraints were added in the instruction screen, and this might have interacted with participants' level of comprehension, whereas the latter work had very high non-compliance rate (43%).…”
Section: Review Of the Empirical Evidencementioning
confidence: 99%
“…First, the Dictator game abstracts from strategic interaction, which enables us to isolate the effect of a given cognitive processing manipulation on social preferences. Second, due to the element of strategic interaction the Public goods game is more difficult to understand, and confusion has been suggested to confound or moderate the effect of time constraints on behavior (Everett et al, 2017;Goeschl & Lohse, 2018;Strømland et al, 2016). By studying a Dictator game, confusion is unlikely to be a possible source of variation in the treatment effect.…”
Section: Experimental Designmentioning
confidence: 99%
“…Similar treatments in the Dictator game also contain mixed evidence; some find no effect (Hauge et al, 2016;Merkel & Lohse, 2018;Tinghög et al, 2016) and others report an effect (Schulz et al, 2014), while a meta-analysis suggests that there is an effect of intuitive processing on altruism only for women (Rand et al, 2016). A large string of papers has suggested that the effect of intuitive decisions on prosocial behavior is heterogeneous (Alós-Ferrer & Garagnani, 2018;Chen & Krajbich, 2018;Rand, 2016;Rand et al, 2016;Rand, 2018;McAuliffe et al, 2018;Strømland, Tjøtta & Torsvik, 2016;Goeschl & Lohse, 2018), which could account for the mixed findings in this literature.…”
Section: Introductionmentioning
confidence: 99%